Genomic and transcriptomic analyses of epsilon-poly-L-lysine producing Streptomyces albulus - Crosse, Amanda Jane (My University, 2018)
Biodiesel production has increased significantly in the past 15 years since it offers a renewable solution to fossil fuels. This production increased the availability of the process’s by-product, crude glycerol. Crude glycerol contains harmful contaminants and with expensive disposal options, often ends in landfill sites where it causes environmental problems. Crude glycerol conversion to valuable products enhances value and aides with disposal problems. Streptomyces albulus was shown to utilize biodiesel-derived crude glycerol as a sole carbon source. Commercially the bacterium is used to synthesize useful secondary metabolites from glucose, e.g. ε-poly-L-lysine (ε-PL). This work aimed to provide a genomic platform for genetic engineering to optimize the production of key secondary metabolites. The first draft genome of S. albulus was sequenced and annotated, together with several relevant transcriptomes. Bio-informatic assessment identified potential genes and pathways involved in glycerol, glucose and ε-PL metabolism. Additionally, 56 silent secondary metabolite gene clusters not previously known, were also identified. Transcriptionally active gene candidates were confirmed by sequencing transcriptomes for different carbon sources (glucose and pure glycerol) over the course of exponential to stationary growth phases – phases linked to ε-PL metabolism. Analyses revealed that the glucose transporter and glycerol uptake facilitator proteins’ differential expressions halved with a pH drop. Glycerol kinase’s and glycerol-3-phosphate dehydrogenase’s (aerobic isoenzyme) relative expression levels decreased with a similar factor, though glycerol-3-phosphate dehydrogenase (anaerobic isoenzyme) showed an increase. Aspartokinase relative expression levels during ε-PL synthesis remained high for both carbon sources, thereby providing S. albulus with sufficient L-lysine monomers during production. Interestingly, ε-PL synthase and both ε-PL degrading enzymes were expressed throughout the growth cycle of S. albulus with both carbon sources, but with ε-PL synthase levels higher at pH 3 than pH 5. This infers that the activity of these enzymes may be more reliant on pH, or substrate availability, than gene expression levels. Genomics, transcriptomics and culturing analyses revealed S. albulus as a halotolerant microorganism. Indeed, three of the four genes of the ectoine pathway, a hydroprotectant, were upregulated with increased salt concentrations. Interestingly the glycerol operon is also upregulated under the high salt concentrations.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy, Johannesburg, 2018
Keywords: Biodiesel fuels; Biosynthesis